Sterile Inflammation of Brain, due to Activation of Innate Immunity, as a Culprit in Psychiatric Disorders - Ratajczak, Mariusz Z.; Pedziwiatr, Daniel; Cymer, Monika; Kucia, Magda; Kucharska-Mazur, Jolanta; Samochowiec, Jerzy (Frontiers in Psychiatry, 2018)
Evidence has accumulated that the occurrence of psychiatric disorders is related to chronic inflammation. In support of this linkage, changes in the levels of circulating pro-inflammatory cytokines and chemokines in the peripheral blood of psychiatric patients as well as correlations between chronic inflammatory processes and psychiatric disorders have been described. Furthermore, an inflammatory process known as “sterile inflammation” when initiated directly in brain tissue may trigger the onset of psychoses. In this review we will present the hypothesis that prolonged or chronic activation of the complement cascade directly triggers inflammation in the brain and affects the proper function of this organ. Based on the current literature and our own work on mechanisms activating the complement cascade (ComC) we hypothesize that inflammation in the brain is initiated by the mannan-binding lectin pathway of ComC activation. This activation is triggered by an increase in brain tissue of danger-associated molecular pattern (DAMP) mediators, including extracellular ATP and high-mobility group box 1 (HMGB1) protein, which are recognized by circulating pattern-recognition receptors (PRRs), including mannan-binding lectin (MBL), that activate the ComC. On the other hand, this process is controlled by the anti-inflammatory action of heme oxygenase 1 (HO-1). In this review we will try to connect changes in the release of DAMPs in the brain with inflammatory processes triggered by the innate immunity involving activation of the ComC as well as the inflammation-limiting effects of the anti-inflammatory HO-1 pathway. We will also discuss parallel observations that during ComC activation subsets of stem cells are mobilized into peripheral blood from bone marrow that are potentially involved in repair mechanisms.